2022
DOI: 10.3389/fphys.2022.974160
|View full text |Cite
|
Sign up to set email alerts
|

Multitargeting nature of muscarinic orthosteric agonists and antagonists

Abstract: Muscarinic receptors (mAChRs) are typical members of the G protein-coupled receptor (GPCR) family and exist in five subtypes from M1 to M5. Muscarinic receptor subtypes do not sufficiently differ in affinity to orthosteric antagonists or agonists; therefore, the analysis of receptor subtypes is complicated, and misinterpretations can occur. Usually, when researchers mainly specialized in CNS and peripheral functions aim to study mAChR involvement in behavior, learning, spinal locomotor networks, biological rhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 257 publications
0
3
0
Order By: Relevance
“…For orthosteric ligands, this usually is not a serious impediment because residues required for natural ligand binding and structural integrity of receptors are highly conserved, whereas residues critical for allosteric signalling are poorly conserved (Leandera et al, 2020). In general, differentiating orthosteric natural agonist sites for families of receptors with a common agonist (such as the 5‐member family of acetylcholine receptors) is difficult due to the similarity of the conserved acetylcholine binding sites (Gentry et al, 2013; Myslivecek, 2022). However, because bias involves protein allostery, there are data to suggest that bias transduction could be more sensitive to receptor structure and amino acid homology than standard orthosteric agonism, even through nuances of agonists binding differently at the same binding site (metabotropic glutamate receptor 5 (mGlu 5 ); Hellyer et al, 2020).…”
Section: Bias Translation: Possible Reasons For Failurementioning
confidence: 99%
“…For orthosteric ligands, this usually is not a serious impediment because residues required for natural ligand binding and structural integrity of receptors are highly conserved, whereas residues critical for allosteric signalling are poorly conserved (Leandera et al, 2020). In general, differentiating orthosteric natural agonist sites for families of receptors with a common agonist (such as the 5‐member family of acetylcholine receptors) is difficult due to the similarity of the conserved acetylcholine binding sites (Gentry et al, 2013; Myslivecek, 2022). However, because bias involves protein allostery, there are data to suggest that bias transduction could be more sensitive to receptor structure and amino acid homology than standard orthosteric agonism, even through nuances of agonists binding differently at the same binding site (metabotropic glutamate receptor 5 (mGlu 5 ); Hellyer et al, 2020).…”
Section: Bias Translation: Possible Reasons For Failurementioning
confidence: 99%
“…Increased Receptor Subtype Selectivity: Selectivity of effect through binding at the orthosteric natural agonist recognition site for families of receptors with a common agonist (i.e. five subtypes of muscarinic acetylcholine receptor all bind acetylcholine) is difficult due to the similarity of the conserved acetylcholine binding sites (Gentry et al, 2013;Myslivecek, 2022). It has been reported that while residues required for structural integrity of receptors are highly conserved, residues critical for allosteric signaling are poorly conserved (Leandera et al, 2020).…”
Section: Allosteric Probe Dependencementioning
confidence: 99%
“…For orthosteric ligands this usually is not a serious impediment as residues required for natural ligand binding and structural integrity of receptors are highly conserved whereas residues critical for allosteric signaling are poorly conserved ( Leandera et al, 2020). In general, orthosteric natural agonist recognition sites for families of receptors with a common agonist (such as the 5 member family of acetylcholine receptors) is difficult due to the similarity of the conserved acetylcholine binding sites (Gentry et al, 2013;Myslivecek, 2022). However, since bias involves protein allostery, there are data to suggest that bias transduction could be more sensitive to receptor structure and a.a. homology than standard orthosteric agonism even through nuances of agonists binding differently at the same binding site (metabotropic glutamate receptor 5 (Hellyer et al, 2020).…”
Section: Bias Translation: Possible Reasons For Failurementioning
confidence: 99%